ON QUASI-MAXIMAL MODULES - Shihab, Bothaynah Nijad; Khalaf, Hatam Yahya (Al-Nahrain Journal of Science, 2010)
Let R be a commutative ring with identity, and let M be a unitary R-module. In this paper weintroduce the concept of quasi-maximal module, some properties and characterizations ofquasi-maximal modules are given. Also, various basic results about quasi-maximal modules andregular modules are considered. Moreover, some relations between quasi-maximal modules andother types of modules are considered.